2018
DOI: 10.1186/s12917-018-1369-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical study to evaluate an oscillometric blood pressure monitor in pet rabbits

Abstract: BackgroundRabbits are particularly sensitive to develop hypotension during sedation or anaesthesia. Values of systolic or mean non-invasive arterial blood pressure below 80 or 60 mmHg respectively are common under anaesthesia despite an ongoing surgery. A reliable method of monitoring arterial blood pressure is extremely important, although invasive technique is not always possible due to the anatomy and dimension of the artery. The aim of this study was to evaluate the agreement between a new oscillometric de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Mean and diastolic systemic arterial blood pressure showed a reduction over time mainly during surgery and at the end of the procedure although no statistical differences were observed between groups. An increase in the concentration of volatile anaesthetic in that period may explain the results and confirms the high sensitivity of this species regarding the isoflurane-induced vasodilation [ 4 , 15 ]. Regardless of the device used to secure the airways, values recorded for mean and systolic arterial blood pressures remained above 60 and 85 mmHg, respectively, in most rabbits.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Mean and diastolic systemic arterial blood pressure showed a reduction over time mainly during surgery and at the end of the procedure although no statistical differences were observed between groups. An increase in the concentration of volatile anaesthetic in that period may explain the results and confirms the high sensitivity of this species regarding the isoflurane-induced vasodilation [ 4 , 15 ]. Regardless of the device used to secure the airways, values recorded for mean and systolic arterial blood pressures remained above 60 and 85 mmHg, respectively, in most rabbits.…”
Section: Discussionsupporting
confidence: 60%
“…The anaesthetic records of 21 adult (15 females and 6 males) mixed breed pet rabbits classified as American Society of Anesthesiologists (ASA) physical status 1, collected by the authors for two previous studies [ 15 , 20 ], were retrospectively assessed. The animals were considered healthy based on clinical history and physical examination, and all rabbits did not show abnormal respiratory sounds or nasal and ocular discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-HDO oscillometric device (PetTrust Blood Pressure Monitor, Aster Electrical, Taiwan) was tested in anaesthetized rabbits by Bellini et al (2018). As in our study, the device met the ACVIM recommendations for MAP and DAP but not for SAP, but the recommendations of the AAMI were only met for MAP, while the HDO device evaluated in our study met the AAMI requirements for both MAP and DAP.…”
Section: Discussionmentioning
confidence: 53%
“…At the ophthalmology level, they have also made it possible to understand the pathophysiology of such dire diseases as glaucoma (8,16,32) . Systemic blood pressure can affect the structure and function of the eye as has been reported in different studies indicating that it has an influence on intraocular pressure, becoming a risk factor for the development and progression of glaucoma (2,6,17) . In these studies it has been indicated that not only hypertension, but also hypotension are risk factors for the development of glaucoma, since it can generate a reduction in the perfusion pressure of the central retinal artery and the posterior portion of the optic nerve (produced by cardiovascular changes that increase resistance to blood flow and / or reduce perfusion) (5,17) .…”
Section: Discussionmentioning
confidence: 92%